Assessment of anaemia in adolescent girls - Upadhye, Jayant V.; Upadhye, Jayshree J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The world’s adolescent population is facing a series of serious nutritional challenges which are not only affecting their growth and development but also their livelihood as adults. Yet, adolescents remain a largely neglected, difficult to measure and hard to reach population, in which the needs of adolescent girls in particular, are often ignored. Anemia in adolescent girls contributes to maternal and foetal mortality and morbidity in future. The objective of the study was to estimate the frequency of anemia among adolescent girls, to study the socio-demographic factors associated with anemia and to evaluate the cause and type of anaemia. Methods: A cross-sectional survey was conducted in an urban area in a school. A total of 300 girls (12-18 years) were included in this study. Statistical analysis was done using percentage, standard error of proportion, Chi-square test and student’s t-test. Results: The prevalence of anemia was found to be 90%. A significant association of anemia was found with socio-economic status and literacy status of parents. Mean height and weight of subjects with anemia was significantly less than subjects without anemia. A high prevalence of anemia among adolescent females was found, among those whose parents were less educated. Conclusions: The overall prevalence of anemia among adolescent females was found to be 90%. There is significant association of anemia with socio-economic status and parents’ educational status. There is need to increase awareness of anemia in adolescent girls and parents.